2006
DOI: 10.1136/jnnp.2005.075929
|View full text |Cite
|
Sign up to set email alerts
|

The Lille apathy rating scale (LARS), a new instrument for detecting and quantifying apathy: validation in Parkinson's disease

Abstract: Background: Apathy is usually defined as reduced interest and participation in various activities. It is a frequent consequence of neurological and psychiatric disorders. Although various scoring methods have been proposed, there is a lack of validated, standardised instruments for detecting apathy and assessing its severity. Objective: To develop an apathy rating scale using a structured standardised interview capable of distinguishing between the condition's various features. Methods: The Lille Apathy Rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
398
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(425 citation statements)
references
References 21 publications
16
398
2
9
Order By: Relevance
“…Participants completed the Apathy Motivation Index (AMI),6 which assesses apathy in terms of behavioral activation (BA: tendency to self‐initiate goal‐directed behavior), social motivation (SM: level of engagement in social interactions), and emotional sensitivity (ES: feelings or affective responses), the Lille Apathy Rating Scale (LARS)12 (patients N  =   87), the Snaith–Hamilton Pleasure Scale (SHAPS)14 (patients N  =   84, controls N  =   67), and the Geriatric Depression Scale–Short Form (GDS‐15)15 (patients n  = 80, controls N  =   87).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed the Apathy Motivation Index (AMI),6 which assesses apathy in terms of behavioral activation (BA: tendency to self‐initiate goal‐directed behavior), social motivation (SM: level of engagement in social interactions), and emotional sensitivity (ES: feelings or affective responses), the Lille Apathy Rating Scale (LARS)12 (patients N  =   87), the Snaith–Hamilton Pleasure Scale (SHAPS)14 (patients N  =   84, controls N  =   67), and the Geriatric Depression Scale–Short Form (GDS‐15)15 (patients n  = 80, controls N  =   87).…”
Section: Methodsmentioning
confidence: 99%
“…We also assessed how different apathy domains were related to depression and anhedonia. The AMI identifies apathy in behavioral , social, and emotional domains and was developed from work based on the Lille Apathy Rating Scale (LARS), a well‐validated structured interview of apathy in PD 12. The willingness to exert effort for reward correlates with the behavioral dimension of the AMI, whereas the willingness to put in effort for other people correlates with the social apathy dimension of the AMI,13 suggesting meaningfully behavioral correlates.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Unifi ed Parkinson's Disease Rating Scale (UPDRS) apathy item also met criteria to be classifi ed as recommended, the task force concluded that the UPDRS should be considered for screening purposes only. Scales that met criteria to be classifi ed but were not recommended were the Apathy Evaluation Scale, 1 the Lille Apathy Rating Scale (LARS), 123 and item 7 in the Neuropsychiatric Inventory. 124 The LARS has since been used in Parkinson's disease by research groups diff erent from those who designed and validated the scale, 125 so this scale would now meet criteria for recommendation.…”
Section: Review Diagnosis Of Apathy In Parkinson's Diseasementioning
confidence: 99%
“…The Lille Apathy Rating Scale (LARS; Sockeel et al, 2006) The LARS is a semi-structured interview assessing specific components of apathy. This scale includes 33 items, divided into nine domains (i.e., everyday productivity, interests, taking initiative, novelty seeking, voluntary actions, emotional responses, concern, social life, and self-awareness).…”
Section: Apathy and Clinical Measuresmentioning
confidence: 99%
“…The global score ranges from -36 to +36, with a higher score representing a greater degree of apathy. The LARS has been validated in French with 159 patients with probable Parkinson's disease (Sockeel et al, 2006). However, only exploratory analyses were conducted and, to date, no confirmatory analysis has validated the LARS's factor structure.…”
Section: Apathy and Clinical Measuresmentioning
confidence: 99%